How to achieve economic growth through industrial synergy and agglomeration: Evidence from China - Peng, Xiaowei; Lim, Jae-Wook; Li, Ning (Edelweiss Applied Science and Technology, 2025)
Against the intertwined backdrop of deglobalization and the digital technology revolution, industrial collaborative agglomeration, as a crucial spatial organizational form for optimizing resource allocation, demands in-depth exploration of its mechanism of action on regional economic growth. This paper constructs a revised E-G index based on the panel data of 31 provinces in China from 2011 to 2023 to measure the level of industrial collaborative agglomeration. By employing fixed-effect models, mediating effect tests, and heterogeneity analysis, it systematically investigates the impact pathways of industrial collaborative agglomeration on economic growth and regional disparities. The study reveals that industrial collaborative agglomeration has a positive promoting effect on regional economic growth, and this conclusion remains robust in variable substitution and lag tests. Mechanism analysis shows that industrial collaborative agglomeration indirectly drives economic growth by enhancing social consumption levels. Heterogeneity analysis finds that the economic promotion effect of industrial collaborative agglomeration is significant in provinces with low urbanization rates and low tax burdens; conversely, the results are insignificant in provinces with high urbanization rates and high-tax environments. This research expands the theoretical framework of industrial collaborative agglomeration, confirms the transmission mechanism driven by consumption, and reveals the role of regional development stages and policy environments in agglomeration effects, providing theoretical support and practical guidance for promoting high-quality economic development.